Assessing the relation between some biochemical variables and vitamin D in patients with recurrent chronic arthritis (Journal of Pharmaceutical Negative Results, 2022)
There are numerous biochemical markers that are either directly or indirectly related to the pathogenesis of rheumatoid arthritis (RA), which is characterized by both local and systemic effects of inflammation. By assessing the level of vitamin D in the serum of patients with recurrent arthritis, we conclude from this study that vitamin D is one of the vitamins that contribute to the emergence of the process of recurrent arthritis. The markers of disease activity such as erythrocyte sedimentation rate (ESR) and rheumatoid factor (RF) were also measured. The study included (60) patients with rheumatoid arthritis of both sexes, with the number of females (22) ranging in age from (31-70) years and the number of males (18) ranging in age from (31-70) years. They were also compared to a control group of (20) healthy men and women, divided into ten (10) males and ten (10) females. For both sexes, their ages ranged from (31-70) years. According to the study's findings, there are significant differences (p<0.05) between the vitamin D3, RF, and ESR groups. The mean levels of ESR and RF were highest in patients(84.05±33.79 and 17.35±5.08) than healthy (38.62±15.53 and 10.55±3.22) respectively. In contrast, the mean levels of vitamin D3 was lowest in patients (21.00±9.68) than healthy (32.40±13.45). The conducted study showed there is no significant difference (p>0.05) between ESR and RF among age groups of patients, but we found there is significant different between vitamin D3 among groups, where >70 and 41-50 years scored highest mean (31.37±9.80 and 23.96±8.82), while 31-40 and 61-70 years scored lowest mean (14.25±6.22 and 13.20±5.39) respectively. We conclude all these The majority of people with rheumatoid arthritis have a vitamin D deficiency, which is one of the factors that contributes to the severity of the disease, according to the research and current study's findings. Vitamin D deficiency in rheumatoid arthritis patients is caused by a lack of vitamin D intake from food sources, insufficient sun exposure, a disorder that impairs vitamin D absorption, and other factors.